2022
DOI: 10.3389/fpls.2022.1037901
|View full text |Cite
|
Sign up to set email alerts
|

A new NLR disease resistance gene Xa47 confers durable and broad-spectrum resistance to bacterial blight in rice

Abstract: Bacterial blight (BB) induced by Xanthomonas oryzae pv. oryzae (Xoo) is a devastating bacterial disease in rice. The use of disease resistance (R) genes is the most efficient method to control BB. Members of the nucleotide-binding domain and leucine-rich repeat containing protein (NLR) family have significant roles in plant defense. In this study, Xa47, a new bacterial blight R gene encoding a typical NLR, was isolated from G252 rice material, and XA47 was localized in the nucleus and cytoplasm. Among 180 rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
0
8
1
Order By: Relevance
“…Xoo induces disease and host susceptibility by injecting TALEs into plant cells; this results in TALE binding to highly-conserved, cognate EBEs in the promoters of known OsSWEET genes. Traditional differential rice varieties for bacterial blight generally encode a series of resistance genes (Nugroho et al 2022 ; Ogawa 1993 ); however, 47 R genes have been identified in rice for bacterial blight resistance (Lu et al 2022 ), which makes it extremely difficult to construct NILs based on R genes. In contrast, susceptibility genes have limited diversity and only three S genes have been identified that are targeted by Xoo in nature; this suggests that effectors with new EBE-binding motifs may not evolve quickly (Oliva et al 2019 ; Xu et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xoo induces disease and host susceptibility by injecting TALEs into plant cells; this results in TALE binding to highly-conserved, cognate EBEs in the promoters of known OsSWEET genes. Traditional differential rice varieties for bacterial blight generally encode a series of resistance genes (Nugroho et al 2022 ; Ogawa 1993 ); however, 47 R genes have been identified in rice for bacterial blight resistance (Lu et al 2022 ), which makes it extremely difficult to construct NILs based on R genes. In contrast, susceptibility genes have limited diversity and only three S genes have been identified that are targeted by Xoo in nature; this suggests that effectors with new EBE-binding motifs may not evolve quickly (Oliva et al 2019 ; Xu et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Breeding plant varieties resistant to pathogens is the most effective and economical approach to control disease. To date, 47 genes conferring resistance to Xoo have been identified, and 13 cloned R genes are associated with TALEs (Jiang et al 2020 ; Zhang et al 2020 ; Ji et al 2020 ; Chen et al 2021 ; Huang et al 2023 ; Lu et al 2022 ). Unfortunately, the constant evolution in pathogen populations weakens the effectiveness of race-specific R genes (Li et al 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…The BB resistance gene Xa43 was recently identified in Zhangpu wild rice (Oryza rufipogon) (Huang et al, 2023). A new NLR disease resistance gene Xa47 has long-term resistance to rice BB disease (Lu et al, 2022b). Xa26(t), which was identified in rice variety Minghui 63, has a dominant effect on the Chinese Xoo strain JL691 at both the seedling and adult stages (Yang et al, 2003) (Figure 4C).…”
Section: Bacterial Blight Resistancementioning
confidence: 99%
“…Recently, a cognate resistance gene, Xa7 , has been identified as displaying durable resistance in rice varieties under field conditions (Zhao et al, 2022). In another study, a novel nucleotide-binding domain and leucine-rich repeat-containing protein (NLR) family Xa47 gene have been identified with broad-spectrum resistance to bacterial blight disease (Lu et al, 2022). Furthermore, a recent proteomic study indicated that infected transgenic rice plants exhibit stimulation in the protein 14–3–3GF14f, which is involved in signal transduction pathways (Molla et al, 2020).…”
Section: Introductionmentioning
confidence: 99%